Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Butik OSM Biz di Kota Banda Aceh - Yusia Fatahillah; Fani Sartika; Nadiya Nadiya (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to determine the effect of price and promotion on consumer purchasing decisions at the OSM Biz Boutique in Banda Aceh City. The method used is causality. The sample for this study was determined using the Slovin formula. The sample used in this study was 82 consumers at the OSM Biz Boutique in Banda Aceh City who agreed to participate as respondents. The analytical method used was multiple linear regression analysis. The results show that both price and promotion partially have a positive and significant effect on purchasing decisions at the OSM Biz Boutique in Banda Aceh City. Price and promotion simultaneously have a positive and significant effect on purchasing decisions at the OSM Biz Boutique in Banda Aceh City. Increased purchasing decisions are determined by price and promotion. The more affordable the price offered, and the more effective and attractive the promotion, the greater the opportunity for the OSM Biz Boutique in Banda Aceh City to increase purchasing decisions.